Authentication of Sumateran Wild Boar (Sus scrofa vittatus) Meat Contamination by Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP) Technique of Cytochrome b Gene - M. W. Adiningsih; R. D. Soejoedono; T. Purnawarman; H. Latif; O. N. Poetri; D. D. Putri (Faculty of Animal Science, Bogor Agricultural University, 2018)
High population of Sumateran wild boar causes the increasing number of hunting and overflowing of wild boar meat availability in the market at a very low price. This condition leads to the falsification of meat. This study was aimed to characterize and differentiate Sumateran wild boar meat (Sus scrofa vittatus) and beef (Bos taurus) since Sumateran wild boar meat is often falsified as a beef in Indonesian traditional market. The domesticated pork meat (Sus scrofa domestica) was also investigated to compare Sumateran wild boar meat and domestic pork. Samples used in this study were DNA (deoxyribonucleic acid) from pork (Sus scrofa domestica), Sumateran wild boar meat (Sus scrofa vittatus), and beef (Bos taurus). Beef and pork were obtained from traditional markets in Bogor city whereas Sumateran wild boar meat was obtained from Way Kanan Regency, Lampung Province. Herein, we performed a thorough investigation on Sumateran wild boar meat (Sus scrofa vittatus) and beef (Bos taurus) using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. This study utilized cytochrome b primer from mitochondria DNA with the size target amplification of 359 bp. This study utilized the restriction endonuclease enzymes, i.e. AluI, BsaJI, HindIII, RsaI, HaeIII, and TaqαI, in order to digest the amplification products from cytochrome b gene. The results showed that HaeIII is the merely specific enzyme to discriminate wild boar meat, domestic pork, and beef since HaeIII was able to digest these three meats in different locations of cyt b gene. However, AluI, BsaJI, HindIII, RsaI, and TaqαI enzymes were not specific enough to differentiate wild boar meat and domestic pork. In conclusion, among six tested enzymes, the use of PCR-RFLP analysis of the cyt b gene followed by digestion using HaeIII restriction enzyme provides a simple, relatively quick, and accurate identification of Sumateran wild boar species.